Antibiofilm effect of ultrasmall 3 C-SiC quantum dots against Escherichia coli and Pseudomonas aeruginosa Gram-negative bacteria - Raypah, Muna E.; Olaoye, Abdulmutolib O.; Khalaf, Hadeel M.; Mohd Faizal, Jamlos; Ahmad Fairuz, Omar; Marzaini, Rashid; Nugroho, Agus; Muhammad, Kozin; Al-Ezzy, Ruqaya M. (Springer Nature, 2025)
In this study, cubic silicon carbide (3 C-SiC) quantum dots (QDs) were synthesized via a hydrothermal chemical etching technique. The 3 C-SiC QDs were characterized using a variety of techniques and instruments. TEM analysis revealed an average diameter of 2.18±0.74 nm. DLS technique demonstrated that the SiC QDs are uniformly distributed and monodisperse with a zeta potential of -26.72±5.55 mV. With a quantum yield of 2.3%, the ultrasmall SiC QDs displayed distinctive fluorescence properties. The result of XPS showed that it is possible to identify the elemental composition of Si and C atoms. FTIR spectra revealed the presence of carboxylic acid, SiH, CH, and CHx groups on the surface of SiC QDs. The XRD patterns revealed that the sample has several peaks that may be connected to SiC, Si, and carbon graphite. 3 C-SiC QDs were employed as an antibiofilm agent against Escherichia Coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) Gram-negative bacteria. P. aeruginosa and E. coli were shown to have minimum inhibitory concentration (MIC) of 16 µg/mL and 64 µg/mL, respectively. At 100 µg/mL, E. Coli and P. aeruginosa bacteria displayed biofilm inhibition of 63.44% and 66.11%, respectively. HeLa, MCF-7, U-2OS, and MCF-10 cells were used to test the biocompatibility of 3 C-SiC QDs, and the findings demonstrated their nontoxicity.